Nilai-Nilai Pendidikan Dalam Sholat Berjamaah Bagi Santri Putra Di Ponpes Al-Ikhlas - Yunus, Muhammad; Taufik, Ahmad; Witjoro, Wisnu Adi; Ferdiansyah, Ahmad (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
The greatest strength in the country is disciplined youth. Pesantren is more than just teaching religion but also obedience in extraordinary discipline. To make the nation's successor youth great in social, discipline, obedience, membership, and skills in religion. This goal is so that every reader can understand the superiority in togetherness of worship. The method used is qualitative research is descriptive with the type of field research. The result of this study is that pesantren education is a forum for Islamic education and learning for the next generation under the guidance of ustad or kiyai which is followed by students as the main activity. The virtue of prayer is the establishment of friendship and readiness to start praying, getting more multiplied rewards, congregational prayer is rewarded with 27 degrees of goodness. The educational values of congregational prayer are to reflect collective obedience to Allah's commands and affirm solidarity in fulfilling religious obligations. Congregational prayer strengthens the sense of brotherhood. There is a value of blessing. reduce the potential for division, and increase the sense of community togetherness. the value of moral and spiritual education. increase concentration, and improve the quality of worship. Stay away from hypocrisy. As well as practicing discipline.